Promising immunotherapeutic targets for treating candidiasis - Feng, Zhe; Lu, Hui; Jiang, Yuanying (Frontiers in Cellular and Infection Microbiology, 2024)
In the last twenty years, there has been a significant increase in invasive fungal infections, which has corresponded with the expanding population of individuals with compromised immune systems. As a result, the mortality rate linked to these infections remains unacceptably high. The currently available antifungal drugs, such as azoles, polyenes, and echinocandins, face limitations in terms of their diversity, the escalating resistance of fungi and the occurrence of significant adverse effects. Consequently, there is an urgent need to develop new antifungal medications. Vaccines and antibodies present a promising avenue for addressing fungal infections due to their targeted antifungal properties and ability to modulate the immune response. This review investigates the structure and function of cell wall proteins, secreted proteins, and functional proteins within C. albicans. Furthermore, it seeks to analyze the current advancements and challenges in macromolecular drugs to identify new targets for the effective management of candidiasis.